2016
DOI: 10.3390/rs8080649
|View full text |Cite|
|
Sign up to set email alerts
|

Time-Dependent Afterslip of the 2009 Mw 6.3 Dachaidan Earthquake (China) and Viscosity beneath the Qaidam Basin Inferred from Postseismic Deformation Observations

Abstract: Abstract:The 28 August 2009 Mw 6.3 Dachaidan (DCD) earthquake occurred at the Qaidam Basin's northern side. To explain its postseismic deformation time series, the method of modeling them with a combination model of afterslip and viscoelastic relaxation is improved to simultaneously assess the time-dependent afterslip and the viscosity. The coseismic slip model in the layered model is first inverted, showing a slip pattern close to that in the elastic half-space. The postseismic deformation time series can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(162 reference statements)
2
6
0
Order By: Relevance
“…Afterslip distributed around and slightly overlapping the coseismic slip patch is in line with theoretical models including but not limited to the case where a velocity-weakening patch is surrounded by velocitystrengthening fault plane (Avouac, 2015;Helmstetter & Shaw, 2009;Marone et al, 1991) and has already been observed in some cases (e.g., Liu et al, 2016;Miyazaki et al, 2004;Thomas et al, 2014). In this case our interpretation is limited by the similarity of surface displacement patterns produced by different models.…”
Section: An Afterslip Model For the Postseismic Interferogramssupporting
confidence: 85%
“…Afterslip distributed around and slightly overlapping the coseismic slip patch is in line with theoretical models including but not limited to the case where a velocity-weakening patch is surrounded by velocitystrengthening fault plane (Avouac, 2015;Helmstetter & Shaw, 2009;Marone et al, 1991) and has already been observed in some cases (e.g., Liu et al, 2016;Miyazaki et al, 2004;Thomas et al, 2014). In this case our interpretation is limited by the similarity of surface displacement patterns produced by different models.…”
Section: An Afterslip Model For the Postseismic Interferogramssupporting
confidence: 85%
“…The 10 November 2008 earthquake occurred south of the Olongbulak Shan with a depth of ∼12 km and produced short‐term and low‐amplitude down‐dip afterslip (Daout, Steinberg, Isken, et al., 2020). Conversely, the 28 August 2009 shallow event occurred at a depth of ∼5 km and produced afterslip around the co‐seismic area (Daout, Steinberg, Isken, et al., 2020; Elliott, Parsons, et al., 2011; Liu, Xu, Li, et al., 2016) (Figure 1b). Despite the deep origin of the 2008 post‐seismic, it is important to note that the short‐term post‐seismic observed in the Envisat data during the 2009–2011 period, might be a combination of the post‐seismic surface displacements from both Haxi earthquakes.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by the authors (Daout, Sudhaus, Kausch, et al., 2019), shallow creep is in agreement with a rate‐strengthening fault behavior of the uppermost part of the crust, but the duration, the amplitude, and the spatial extent of the observed surface displacements following the 2003 earthquake, during the 2003–2011 Envisat period, is a notable particularity, despite the low strain rate of the area. The 10 November 2008 and the 28 August 2009 Haixi earthquakes occurred in close proximity to each other within the Olongbulak Shan, to the west of the Delingha rupture (Figure 1), and were followed by a period of an increased rate of seismicity in the region and aseismic slip (Daout, Steinberg, Isken, et al., 2020; Daout, Sudhaus, Kausch, et al., 2019; Elliott, Parsons, et al., 2011; Feng, 2015; Guihua et al., 2013; Liu, Xu, Li, et al., 2016; Liu, Xu, Wen, & Fok, 2015; Liu, Xu, Wen, & Li, 2016). Daout, Steinberg, Isken, et al.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical accuracy can be as high as a centimeter to as low as a millimeter. This technique has been widely used to identify many geophysical processes that usually cause long-wavelength crustal deformation, including strain accumulation along locked continental faults, coseismic deformation caused by the occurrence of faulting in the lithosphere, and postseismic deformation caused by afterslip and viscoelastic relaxation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%